Avaliação da diversidade genética de isolados de Brucella abortus em um foco de brucelose - Elaine Maria Seles Dorneles (2011)
The purpose of this study was to evaluate the genetic diversity of isolates of B. abortus from a single outbreak of brucellosis in function of time and clinical specimen from which the isolate was obtained, and thus indirectly investigate the stability of the MLVA 16 markers. Two hundredand sixty-one clinical samples of cattle belonging to an outbreak of brucellosis were collected during 13 months, 161 samples of vaginal swabs and 100 milk samples, which were submitted to culture, biotyping, molecular identification and genotyping by MLVA 16. Nine B. abortusstrains isolates obtained from vaginal swabs were identified as RB51. Eighteen isolates, seven obtained from milk samples and eleven from vaginal swabs, were identified as B. abortus biovar 3 field strain. One isolate obtained from vaginal swab was identified as B. abortus biovar 1 field strain. Three distinct genotypic profiles were obtained from the outbreak of brucellosis: the genotype A, was observed in all isolates identified as B.abortus biovar 3; the genotype C was found in all isolates of RB51 vaccine strain; and the genotype B was observed in the isolate ofB. abortus field strain / biovar 1. The analysis of epidemiological and molecular data indicates that genotype B is not related to the other genotypes found in focus, and that it is probably introduction of a new field strain in the herd. Thus, it is possible concluded that there is low genetic diversity among isolates, even when evaluated over a period of 13 months and from different clinical materials, and that the markers that make up the MLVA 16 are stable when subjected to selective pressure in natural infections.